2022
DOI: 10.1186/s12888-022-03845-y
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ desires for anxiolytic premedication – an observational study in adults undergoing elective surgery

Abstract: Background Most patients experiencing preoperative anxiety would welcome support in coping with their anxiety. Anxiolytic medication is a common way to address preoperative anxiety. However, the proportion of patients who welcome anxiolytic medication preoperatively and the preferred time of taking it have not been studied thoroughly. Methods Adult patients (n = 1000) scheduled to undergo elective surgery under general anesthesia were eligible to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…1,2 Patients have been shown to find anxiety emotionally distressing, desire anesthesiologists aid in coping with the anxiety, and desire anxiolytic medication whether or not they perceived a high level of anxiety. 1,10 One RCT showed a reduction in postoperative, patient-controlled-analgesia dosages but not in postoperative pain scores in women who received oral lorazepam the night prior and intramuscular midazolam the morning of a total hysterectomy. 5 Another RCT in women undergoing total hysterectomy demonstrated that anxious women who did not receive preoperative lorazepam had higher pain scores and opioid consumption than anxious and nonanxious women who received preoperative lorazepam as well as nonanxious women who received placebo.…”
Section: Benzodiazepine Anxiolysis Reduces Postoperative Painmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Patients have been shown to find anxiety emotionally distressing, desire anesthesiologists aid in coping with the anxiety, and desire anxiolytic medication whether or not they perceived a high level of anxiety. 1,10 One RCT showed a reduction in postoperative, patient-controlled-analgesia dosages but not in postoperative pain scores in women who received oral lorazepam the night prior and intramuscular midazolam the morning of a total hysterectomy. 5 Another RCT in women undergoing total hysterectomy demonstrated that anxious women who did not receive preoperative lorazepam had higher pain scores and opioid consumption than anxious and nonanxious women who received preoperative lorazepam as well as nonanxious women who received placebo.…”
Section: Benzodiazepine Anxiolysis Reduces Postoperative Painmentioning
confidence: 99%
“…1 Another study showed that the majority of patients desired anxiolytic medication whether or not they perceived themselves as anxious. 10 Our subsequent argument details the lack of evidence that a single, preoperative anxiolytic benzodiazepine when given judiciously causes harm. We detail why alternative anxiolytic methods may not be adequate for all patients and that appropriate treatment of high anxiety offers significant benefits.…”
Section: Pro: Administer Benzodiazepines Judiciously For Preoperative...mentioning
confidence: 99%
See 1 more Smart Citation